Regulation of Nitric Oxide Production by δ-Opioid Receptors during Glaucomatous Injury - Husain, Shahid; Abdul, Yasir; Singh, Sudha; Ahmad, Anis; Husain, Mahvash (PLOS ONE, 2014)
To determine the roles of nitric oxide in glaucomatous injury and its regulation by δ-opioid-receptor activation, animals were treated with: 1) a selective inducible nitric oxide synthase (iNOS) inhibitor (aminoguanidine; AG; 25 mg/kg, i.p.); 2) δ-opioid-receptor agonist (SNC-121; 1 mg/kg, i.p.); or 3) with both drugs simultaneously for 7 days, once daily. The loss in retinal ganglion cell (RGC) numbers and their function in glaucomatous eyes were significantly improved in the presence of AG or SNC-121; however, we did not see any significant additive or synergistic effects when animals were treated with both drugs simultaneously. The levels of nitrate-nitrite were significantly increased in the glaucomatous retina when compared with normal retina (normal retina 86±9 vs. glaucomatous retina 174±10 mM/mg protein), which was reduced significantly when animals were treated either with SNC-121 (121±7 mM/mg protein; P<0.05) or AG (128±10 mM/mg protein; P<0.05). Additionally, SNC-121-mediated reduction in nitrate-nitrite levels was not only blocked by naltrindole (a δ-opioid-receptor antagonist), but naltrindole treatment potentiated the nitrate-nitrite production in glaucomatous retina (235±4 mM/mg protein; P<0.001). As expected, naltrindole treatment also fully-blocked SNC-121-mediated retina neuroprotection. The nitrotyrosine level in the glaucomatous retina was also increased, which was significantly reduced in the SNC-121-treated animals. Additionally, the expression level of iNOS was clearly increased over the control levels in the glaucomatous retina and optic nerves, which was also reduced by SNC-121 treatment. In conclusion, our data support the notion that nitric oxide plays a detrimental role during glaucomatous injury and inhibition of nitric oxide production provided RGC neuroprotection. Furthermore, δ-opioid receptor activation regulates the production of nitric oxide via inhibiting the activity of iNOS in the retina and optic nerve.